Persepsi Mahasiswa dan Tutor tentang Kejadian Kritis Selama Diskusi Tutorial dan Jenis-jenis Interview Terhadap Kejadian Tersebut - Amelia Dwi Fitri; Harsono Mardiwiyoto; Efrayim Suryadi (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2013)
Background: Tutorial group discussion is one of the key features of problem based learning. The tutor-facilitated group discussion is not always work as planned. Critical incident during tutorial is one of the factors that may hinder group dynamics. Six factors hindering group dynamics (unequal participation, lack of cohesion, lack of motivation, lack of elaboration, lack of interaction, and personality problem), play role in critical incidents during tutorial. Tutor’s and students’ perception on critical incidents are affected by each individual point of view on the incidents. The point of view will influence intervention expected by students and actual intervention done by tutor. Tutor’s capability to do proper intervention is one of the factors needed to ensure group discussion to progress well. The aim of this research is to identify students and tutors perception on critical incidents during tutorial and types of intervention done by tutor to overcome these incidents.Method: This is a mixed-method research which combines quantitative and qualitative approaches. 352 students of 4 batches and 21 tutors involved in this research. Students and tutors’ perception on critical incidents were collected using questionnaire consist of 36 Likert-scale items, and 2 open-ended questions. Intervention done by tutors was further explored using focus group discussion with tutor and students, based on quantitative result.Results: Similar perception were found in both students and tutors regarding the factors influenced critical incidents during tutorial the most, which was unequal participation. Nevertheless, different perception was found between students and tutors on factor that hindered discussion which require tutor intervention; students with difficult personality, whereas tutors stated participation imbalance. The other five factors: tutor’s factors, feedback, assessment, quality of scenario, logistics, and scheduling issue were found to have role in critical incidents in tutorial. Tutor’s intervention to critical incidents had been done, even so, further development is needed.Conclusion: Students’ and tutors’ perception on critical incidents were in line in term of the most frequent incidents, but differ in factor that hinder discussion the most and require tutor’s intervention. There were many other factors that influenced critical incidents besides students’ factors. Interventions which had been done by tutors were not adequate in order to overcome arising critical incidents.